Development of Arabic Teaching Modules Based on Constructivism with a Communicative Approach: Pengembangan Modul Ajar Bahasa Arab Berbasis Konstruktivisme dengan Pendekatan Komunikatif - Fahmiyah Tsaqofah Islamiy; Eni Fariyatul Fahyuni (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2024)
As a tool that guides the learning process, the teaching module must contain all the essential components of teaching and learning stages oriented toward student progress. In Arabic language learning, the continuous integration of collaborative and feedback-oriented language learning strategies into language instruction in the teaching and learning process plays a vital role as stimulation that facilitates interaction experiences between students actively using the target language to improve the quality of learning. This research focuses on developing a constructivism-based Arabic teaching module with a communicative approach that is valid, effective, communicative, and contextual on one of the Arabic language materials for grade XI produced by the Ministry of Religion of the Republic of Indonesia in 2020. Product development of teaching modules is carried out using the 4D method, which is further modified into 3D. The results found that based on expert validation, the developed module met the criteria of being very feasible in the material aspect with a score of 97.3, very feasible in the language aspect with a score of 100, and very feasible in the media aspect with a score of 100. In the trial session, a score of 88.5 was obtained for the material component, 89.8 for the presentation component, and 97.2 for the language component. Thus, the module is categorized as feasible and effective for using Arabic and has been adapted to improve skills progress. Keywords: Arabic, Communicative Approach, Constructivism, Teaching Module